In vivo antithrombotic synergy of oral heparin and arginine: Endothelial thromboresistance without changes in coagulation parameters - Daniels, Bruce; Linhardt, Robert J.; Zhang, Fuming; Mao, Wenjun; Wice, Sandra M.; Hiebert, Linda M. (Thrombosis and Haemostasis, 2006)
On the basis of suggested clinical efficacy in an uncontrolled study in ninety-seven patients with unstable angina, an animal study was conducted to investigate antithrombotic synergy between orally administered heparin and arginine. A rat venous thrombosis model tested the difference in thrombus formation when heparin (7.5 mg/kg) and arginine (113 mg/kg) were administered, alone or in combination, by stomach tube with a minimum of 20 rats/group. Oral heparin, arginine, and heparin plus arginine reduced thrombus formation by 50%, 75%, and 90%, respectively,when compared to saline administration. Heparin was recovered from endothelium, yet there was little or no observable plasma anticoagulant activity. An orally administered lowmolecular-weight anticoagulant glycosaminoglycan mixture, sulodexide (7.5 mg/kg), showed an 88% reduction in stable thrombus formation when administered alone but showed no synergy with oral arginine. A 28-day study with oral sulodexide (2.9 mg/ kg) and arginine (43.9 mg/kg), 20 rats/group, showed antithrombotic activity with minimal anticoagulant activity indicating suitability for long term treatment. These findings suggest the endothelial localization of heparin and a synergistic antithrombotic effect for orally administered heparin and arginine.
Keywords: Heparin; thrombosis; endothelium; arginine; oral